Political Dynasties in Governance and Regional Financial Transparency - Permatasari, Lintang Jelita; Zainudin, Arif; Widodo, Agus Setio (Department of Government Studies, Universitas Syiah Kuala, 2025)
The phenomenon of political dynasties in Indonesia occurs not only at the national level but is also deeply rooted at the regional level, providing space for local elites to establish and sustain hereditary power This study aims to analyze the interaction between dynastic politics and bureaucratic processes in regional governments through the lens of good governance principles, particularly transparency and effectiveness. A systematic literature review was employed, incorporating meta-synthesis and meta-analysis of previous findings related to the impact of political dynasties on local governance and financial management. VOSviewer was utilized as an analytical tool to identify research trends, typologies of political dynasties, and their implications. The findings indicate that political dynasties may hinder bureaucratic professionalism and neutrality, while also diminishing public trust in institutions. However, the implementation of transparent information systems, such as the regional financial management agency (BPKAD) websites, enables more effective public oversight, despite challenges related to human resource capacity and technological infrastructure. The study highlights the need for stakeholder collaboration to enhance bureaucratic performance and e-governance implementation in dynasty-dominated regions.